Estrategias para el desarrollo de la consciencia lingüística. - Correa Bautista, Erika Nataly (2023)
Through this research, the effectiveness of strategies based on semantic fields for the acquisition of linguistic skills can be demonstrated, specifically at the level of semantic awareness. The diagnosis of the problem, as well as the design and application of strategies, was done together with the 36 students of the 2nd Parallel Grade “B” of General Basic Education of the September 19 Educational Unit of the Salcedo Canton. The methodology used is quantitative, typical of the positivist paradigm, its design was pre-experimental since a pre-test and a post-test were applied, both instruments contemplated five activities in which sequences of images were shown to the children with the purpose of obtain information about your linguistic and semantic skills. The results showed great findings as rapid progress was evident in the students' achievement of semantic skills.